El proceso administrativo para la sostenibilidad de la empresa Zona Carnes & Mariscos de la cuidad de Loja. - Simancas Aguilar, Rosario Guadalupe (2024)
The administrative process is a tool of transcendental importance for the sustainability of the companies, that is why it has been considered convenient to work on this process in Zona Carnes & Mariscos company. The objective of this research is to carry out the processes of planning, organization, management and control of the company in question. The approach of this study is qualitative and descriptive; the inductive method was used, applying information gathering tools to carry out the diagnosis. The results of the analysis of the external factors show that the organization has a weighted weight of 2.81, which means that the company takes advantage of the environment, thus generating an optimal competitive level. As for the internal analysis, the weighting is 2.30, indicating that the company is below the established standard level, that is, it is internally weak in the management of the administrative process. In conclusion, it is established that the activities are not executed in an efficient and effective manner. Therefore, this proposal has been generated to improve its strengths and minimize weaknesses, providing Zona Carnes & Mariscos with the necessary tools to strengthen its internal structure and, thus, improve its overall performance.